2017
DOI: 10.20964/2017.07.53
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a “Green” and Low–Cost Screen–Printed Graphene Sensor and Its Application to the Determination of Caffeine by Adsorptive Stripping Voltammetry

Abstract: This work reports the development of low-cost graphene-based screen-printed sensors using a "green" fabrication procedure. Three-electrode sensors featuring carbon working and counter electrodes and a Ag reference electrode were fabricated by screen-printing on flexible polymer film. Graphene suspension was prepared following a simple, fast and environment-friendly method of solvent exfoliation of graphite in N-methyl pyrrolidone (NMP). Graphene was further dispersed in Nafion and the solution was used to drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Two limiting cases can be envisaged. In the first the accumulated material is directly oxidized or reduced in its adsorbed state – for example in the cases of capsaicin and caffeine – whereas in the second the material has to first desorb and then transport to the electrode surface. The latter case corresponds to the now common practice of using insulating particles (imprinted polymeric nanobeads in the detection of mercury, for example ) and materials as electrode modifiers.…”
Section: Figurementioning
confidence: 99%
“…Two limiting cases can be envisaged. In the first the accumulated material is directly oxidized or reduced in its adsorbed state – for example in the cases of capsaicin and caffeine – whereas in the second the material has to first desorb and then transport to the electrode surface. The latter case corresponds to the now common practice of using insulating particles (imprinted polymeric nanobeads in the detection of mercury, for example ) and materials as electrode modifiers.…”
Section: Figurementioning
confidence: 99%
“…Lezi et al [ 90 ] described the preparation process and the application of a graphene/Nafion-modified screen-printed electrode (SPE-Nafion/graphene) for CF determination in 0.2 M H 2 SO 4 /0.01 M HCl solution using adsorptive stripping voltammetry. Due to the synergistic effect of Nafion and graphene, the modified SPE exhibited high sensitivity and a low limit of detection for CF ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…GPN and its derivatives have been used as a raw material for sensors in different applications due to their thermal and electrical conductivity, large surface area, fast heterogeneous electron transfer rates, and high mechanical strength [37][38][39][40]. Recent studies showed exceptional results for instance better sensibility, low cost, easy operation, fast response and recovery time, and good selectivity.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…erefore, determining the concentration of caffeine in food samples is necessary to avoid involuntary excessive consumption of this compound. Lezi [39] fabricated a GPN/Nafion sensor to determine the presence of caffeine by adsorptive stripping voltammetry.…”
Section: Molecules and Chemical Elementsmentioning
confidence: 99%